Long‐term outcomes of hepatic resection for colorectal liver metastases at a New Zealand tertiary level public hospital. Issue 4 (17th February 2016) - Foo, Elizabeth W.; Moore, Tom; Harris, Dean; Yi, Ma; Connor, Saxon
Abstract : Background: Colorectal cancer is common with half of all patients developing metastases to the liver. The aim of this study was to document the survival for patients undergoing liver resection for colorectal cancer metastases. Method: A review of all patients undergoing hepatic resection for colorectal liver metastases at a New Zealand tertiary level public hospital over a 9‐year period was performed. Results: Primary survival outcomes assessed were overall survival (OS) and disease‐free survival (DFS). Of the 116 patients followed‐up with a median (range) of 53 (10–116) months, the OS at 5 years was 53%. Median survival was 6.5 years. At end of follow‐up, 57% of patients were alive and 49% were alive without recurrence. The overall rate of recurrence was 39%. Conclusion: This study confirms that excellent long term survival can be achieved with hepatic resection for colorectal liver metastases.